2022
DOI: 10.3389/fbioe.2022.722722
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Transgene Expression by Optimization of Poly A in Transfected CHO Cells

Abstract: The generation of the stable, high-level recombinant protein-producing cell lines remains a significant challenge in the biopharmaceutical industry. Expression vector optimization is an effective strategy to increase transgene expression levels and stability, and the choice of suitable poly A element is crucial for the expression of recombinant protein. In this study, we investigated the effects of different poly A elements on transgene expression in Chinese hamster ovary (CHO) cells. Five poly A elements, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…This property is especially interesting if applied to studying resource allocation and gene expression burden. Recently, several studies have shown how burden in mammalian cells is generated through the sharing of cellular resources both at the transcriptional and translational level. , The ability to isolate exogenous genes from the cellular resources can be used, for example, in bioproduction where the stable generation of a protein over time can have dramatic consequences on its yield and downstream applications . We showed that using mOptoT7 to orthogonally generate RNA species (in an inducible manner) not only helps in reducing burden, but can also help in gaining a better understanding of the effect of transcriptional resources on burden as a whole.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This property is especially interesting if applied to studying resource allocation and gene expression burden. Recently, several studies have shown how burden in mammalian cells is generated through the sharing of cellular resources both at the transcriptional and translational level. , The ability to isolate exogenous genes from the cellular resources can be used, for example, in bioproduction where the stable generation of a protein over time can have dramatic consequences on its yield and downstream applications . We showed that using mOptoT7 to orthogonally generate RNA species (in an inducible manner) not only helps in reducing burden, but can also help in gaining a better understanding of the effect of transcriptional resources on burden as a whole.…”
Section: Discussionmentioning
confidence: 95%
“… 8 , 9 The ability to isolate exogenous genes from the cellular resources can be used, for example, in bioproduction where the stable generation of a protein over time can have dramatic consequences on its yield and downstream applications. 59 We showed that using mOptoT7 to orthogonally generate RNA species (in an inducible manner) not only helps in reducing burden, but can also help in gaining a better understanding of the effect of transcriptional resources on burden as a whole. In this context, the contribution of IRES sequences that are included in the mOptoT7 reporter are not considered in this study and require further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…At 48-h post transfection, the transfection efficiency of each expression vector was observed under a fluorescence microscope (ECLIPSE Ti; Nikon, Tokyo, Japan), and mean fluorescence intensity (MFI) was detected by flow cytometry as previously described ( Wang et al, 2019 ; Wang et al, 2022 ). Briefly, a total of 100,000 fluorescent events were obtained using a 530/15 bandpass filter for the green fluorescent signal, which was acquired with an emission wave length of 530 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The establishment of transfected cell lines with high-level expression of the gene of interest (GOI) is often an arduous process due to the heterogeneity of transgene expression. To obtain stable and highly transfected GOI cell lines, cell line engineering, growth medium and production process modification, and expression vector design were performed ( Jia et al, 2018 ; Guo et al, 2020 ; Wang et al, 2022 ). Among these strategies, the expression vector design is an effective method to increase GOI expression level and stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation